Consultório na rua: uma revisão integrativa da literatura - Portto, Victor Mateus Macario (2024)
The creation of the Unified Health System (SUS) in 1988 initiated the process of implementing the guarantee of universal public health with equity and comprehensive care, but it was only from the 1990s that several Brazilian cities began the process of considering care for the homeless population as a health policy. The Street Clinic emerges as a necessary health strategy, aiming to reach the homeless population who are often excluded from access to traditional health services for various reasons. In 2011, the National Policy for the Homeless Population was instituted and adopted by the Ministry of Health as a service relevant to Primary Health Care only in 2012. The present study aims to understand which themes permeate the scientific discussions about the Street Clinic in the period from 2012 to 2024. The method is an integrative review of the existing literature on the subject. The search for works for the research was carried out in the Virtual Health Library and in the PubMed and SciELO databases. Initial results: the identification and interpretation of the categories - vulnerability and stigma; for the right to universal access to health; the territory as a space for health care; and the experience of caring in the Street Cliinic - which permeate the existing literature on the subject and the suggestion of possible studies and pending discussions about Street Clinic from the researcher's perception in the dichotomy between theory and practice.